Continuous multi-column sorption-enhanced dimethyl ether synthesis (SEDMES): Dynamic operation - van Kampen, Jasper; Overbeek, Johan; Boon, Jurriaan; van Sint Annaland, Martin (Frontiers in Chemical Engineering, 2023)
In this work the continuous production of dimethyl ether (DME) by sorption-enhanced DME synthesis (SEDMES) technology has been demonstrated for the first time with a multi-column test-rig. A continuous single-pass carbon yield up to 95%, higher than ever reported before, has been achieved. The multi-column experiments have also shown that SEDMES can be operated at lower temperatures (220 °C) than previously reported. This allows a higher temperature rise, making higher conversions possible while allowing even larger reactor tube diameters. Whereas the anticipated multi-tubular reactor concept is complex and costly, larger reactors could facilitate the economic valorisation. The SEDMES reactor model cannot only describe the transient behaviour of the process during the cyclic steady-state well, but also the dynamic approach towards the cyclic steady-state is adequately captured. Capturing the dynamic operation is of large interest with respect to process flexibility, especially for Power-to-X systems.